SISTEMA NANOESTRUTURADO A BASE DE NANOPONTOS DE CARBONO PARA O TRANSPORTE E LIBERAÇÃO DO QUIMIOTERÁPICO 5- FLUOROURACIL. - CUTRIM, Elaine Sá Menezes (2019)
Chemotherapy is one of the most conventional approaches to cancer treatment. Nevertheless, the use of chemotherapeutic has numerous disadvantages such as low therapeutic efficiency, high non-productive drug distribution and undesirable side effects to the patient. Nanotechnology has shown remarkable progress in this area using nanoparticles in drug delivery systems. These systems are able to direct the drug to a specific biological target, reduce toxicity and maintain therapeutic concentration levels for a long time. Recently, the application of carbon quantum dots (CQDs) for biomedical purposes has gained much attention due to their biocompatibility, easy surface functionalization and photoluminescence properties. 5- Fluoruracil (5-FU) is an antineoplastic widely used in the treatment of solid tumors (colorectal, breast, stomach, etc.), which has low specificity and high toxicity. Thus, the aim of this study was to obtain a nanodevice for transport and release of 5-FU in order to improve its therapeutic efficiency using as strategy the fabrication of a hybrid material by drug anchorage on the surface of CQDs. Carbon quantum dots were synthesized by the solvothermic treatment of citric acid and urea, while the 5-FU-CQD hybrid material was prepared by self-assembly adding the CQDs into drug solution. Several characterization techniques were employed to obtain information about the morphology, structure and optical properties of the materials. The results indicated that the drug anchorage on CQDs’ surface occurred through electrostatic interactions and/or hydrogen bond between the CQDs and 5-FU functional groups. Acid pH favored drug release during the first 12 hours of experiment, indicating a tendency for 5-FU to be released into the tumor microenvironment. The cytotoxicity of CQD and 5-FU-CQD hybrid material was evaluated against normal fibroblast (GM07492) and mammary adenocarcinoma (MCF-7) line cells. The CQDs were non-toxic in the range of 12.5 to 800 mg.L-1, indicating that these materials are indeed biocompatible and can be used as nanocarrier for 5-FU in biological systems. For the 5-FU-CQD hybrid, a reduction in toxicity to normal cells were observed compared to pure 5-FU, suggesting that drug anchoring in CQDs reduced the drug-associated toxicity. Regarding cancer cells, or tumor cells the 5-FU-CQD hybrid material exhibited an antitumor effect equivalent to pure drug, suggesting maintenance of the antitumor action of the drug with reduced toxicity to healthy cells.